The methodology of teaching fine arts as a factor in the formation of art and pedagogical education in Ukraine in the early 20th century - Panyok, Tetiana; Grineva, Valentyna (Professional Art Education, 2025)
The article explores the development of teaching methods in fine arts as a key factor in the formation of art-pedagogical education in Ukraine at the beginning of the 20th century. During this period, the issue of teaching methodology in Ukrainian art institutes became the subject of profound reflection and professional analysis in the publications of prominent artist-educators. The revolutionary events of the early 20th century encouraged the construction of a higher art-pedagogical education system based on the foundations of Ukrainian national culture.Methods and methodology. To address the defined objectives and achieve the aim of the study, a set of interrelated scientific methods was employed at various stages of the research: Historical and pedagogical analysis – used to substantiate the periodization of the development of future artist-teachers' training within the context of the evolution of higher art education in Ukraine; Structural method – applied to define the essence of the key concepts of the research and to analyze the main facts in the history of higher art education development; Comparative method – aimed at identifying common and specific features in each of the defined periods concerning the training of future artist-teachers, as well as theoretical and practical achievements in various higher art educational institutions.Scientific novelty. For the first time, the theoretical and methodological foundations of training future artist-teachers within the development of higher art education in Ukraine are revealed. The content, forms, methods, tools, and prospects for creatively applying the experience of training artist-teachers in the context of higher art education reform are described. Based on archival materials, the formation of a national methodology for teaching fine arts in Ukraine at the beginning of the 20th century is also characterized.Results. 20th century marked a pivotal moment in Ukrainian art education, characterized by a synthesis of the Ukrainian aesthetic worldview–rooted in sacred and folk traditions–with leading European art movements such as Cubism (A. Exter, O. Hryshchenko), Futurism (M. Semenko), Ukrainian versions of Expressionism (O. Novakivskyi), and Constructivism (V. Tatlin). Ukraine also gave rise to original, indigenous avant-garde movements, including the cubist sculpture of O. Arkhipenko, the Cubo-Futurism of D. Burliuk and O. Bohomazov, Suprematism (K. Malevich), Constructivism (V. Tatlin), “color-writing” by V. Palmov, the Neo-Byzantinism of the Boichuk brothers, and the “Ukrainian style” seen in the works of H. Narbut, the Krychevsky brothers, and O. Saienko.At the beginning of the 20th century, the creative work of many Ukrainian artists demonstrated a synthesis of European avant-garde aesthetics with ethno-national consciousness and symbolic archetypes of the "folk soul" expressed through sacred semiotic codes. The study identifies the significant role of artist-educators who developed original teaching methods based on the synthesis of Ukrainian ethnopedagogy, sacred art, and advanced European educational practices. These approaches contributed to the emergence of a national system of art education aimed at reviving Ukrainian cultural identity and discovering a distinctive national artistic style. Innovative methodological foundations included principles of synesthesia, formal-technical analysis of color and space, and mastery of artistic techniques. The goal of these methods was to define effective educational strategies that enabled students not only to acquire basic artistic knowledge and skills, but also to understand the essence of the subject and develop professional competence. For the first time, academic programs in art institutions incorporated educational standards that integrated theoretical instruction with practical training, thereby enhancing the preparation of qualified specialists in the field of fine arts. The article highlights the importance of teaching methodology as an integrative component of both pedagogy and art in the formation of a modern Ukrainian system of art-pedagogical education, contributing to the development of a national methodology in higher artistic training.Conclusions. The conducted research demonstrates that the methodology of teaching fine arts at the beginning of the 20th century became a significant factor in the development of art and pedagogical education in Ukraine. During this period, profound transformations in the educational process occurred, driven by both socio-cultural challenges and the aspiration for national revival. The creative approaches of educators were grounded in a deep exploration of Ukrainian sacred art and a pursuit of a national style as a visual code of modern Ukrainian identity. The formation of a national methodology for teaching fine arts in early 20th-century Ukraine played a key role in shaping art and pedagogical education. This methodology not only served as the foundation for training a new generation of teachers but also laid the groundwork for the emergence of a Ukrainian art school–one that integrated rich national traditions with a modernist drive for innovation and universality.
Keywords: ethnopedagogy; method; methodology; art; pedagogy; art and pedagogical education; fine arts specialists